Rigorous and efficient full-wave analysis of trapezoidal patch antennas. - Bilotti, F.
A rigorous full-wave analysis in the spectral domain for trapezoidal patch antennas is presented. Particularly, a new set of entire domain basis functions for an efficient implementation of the method of moments (MoM) is carried out by properly imposing the boundary conditions. The simulated results obtained through the presented method are compared to the measurements showing a good agreement. Finally, a parametric analysis of the main antenna features (matching, radiation pattern, cross-polarization levels) is also carried out
Keywords: MoM; Antenna features; Boundary conditions; Cross-polarization levels; Efficient full-wave analysis; Entire domain basis functions; Integral equations; Matching; Method of moments; Parametric analysis; Radiation pattern; Rigorous full-wave analysis; Simulated results; Spectral domain analysis; Trapezoidal patch antennas